Elevated CO2 priming as a sustainable approach to increasing rice tiller number and yield potential - Sloan, Jennifer M.; Muhamad Mujab, Azzami Adam; Mashitah, Jusoh; Zulkarami, Berahim; Wilson, Matthew J.; Toh, Liang Su; Nur Zahirah, A. Jalil; Afiq, Kamaruzali; Asyraf, Ahmad Tajuddin; Zhu, Xin-Guang; Yaapar, Nazmin; Fleming, Andrew J. (Springer Science and Business Media, 2023)
Tillering and yield are linked in rice, with significant efforts being invested to understand the genetic basis of this phenomenon. However, in addition to genetic factors, tillering is also influenced by the environment. Exploiting experiments in which seedlings were first grown in elevated CO2 (eCO2) before transfer and further growth under ambient CO2 (aCO2) levels, we found that even moderate exposure times to eCO2 were sufficient to induce tillering in seedlings, which was maintained in plants grown to maturity plants in controlled environment chambers. We then explored whether brief exposure to eCO2 (eCO2 priming) could be implemented to regulate tiller number and yield in the field. We designed a cost-effective growth system, using yeast to increase the CO2 level for the first 24 days of growth, and grew these seedlings to maturity in semi-field conditions in Malaysia. The increased growth caused by eCO2 priming translated into larger mature plants with increased tillering, panicle number, and improved grain filling and 1000 grain weight. In order to make the process more appealing to conventional rice farmers, we then developed a system in which fungal mycelium was used to generate the eCO2 via respiration of sugars derived by growing the fungus on lignocellulosic waste. Not only does this provide a sustainable source of CO2, it also has the added financial benefit to farmers of generating economically valuable oyster mushrooms as an end-product of mycelium growth. Our experiments show that the system is capable of generating sufficient CO2 to induce increased tillering in rice seedlings, leading eventually to 18% more tillers and panicles in mature paddy-grown crop. We discuss the potential of eCO2 priming as a rapidly implementable, broadly applicable and sustainable system to increase tillering, and thus yield potential in rice.